Rethinking ‘need’ for clinical support in transgender and gender non-conforming children without clinical classification: Learning from ‘the paper I almost wrote’ - Horowicz, Edmund (Bioethics, 2021)
There have been ongoing debates as to how, or even whether, we should clinically classify gender diversity in children through clinical classification manuals. So-called ‘depathologizing’ is argued as being vital to address the stigma that these children are somehow disordered or sick. Yet one argument in favour of continued clinical classification for transgender and gender non-conforming children is that it better facilitates access to specialist psychological support. I argue that whilst continued clinical classification offers a seemingly pragmatic solution to ensuring access, it does in fact obscure our understanding of the individual needs of these children. In this paper I address fundamental issues that aim to better our understanding of need and thus why a child may benefit from specialist support. I do so by critiquing a paper I nearly wrote, which argued for the ongoing continued classification of gender incongruence in children. Ultimately, I argue that specialist psychological support and care should be driven by the needs of the individual child, as determined by the child and those involved with their care. By bettering our understanding as to why specialist psychological support may be beneficial for some, we move past the focus of such specialist support being provided because of the child’s gender diversity. Methodologically the paper may be unusual, in comparison to traditional normative counter-argumentative bioethical position papers, but by presenting an argument for depathologization of gender diversity of children in this way there is also an alternative insight into the methods of bioethics.